عمرو بن الإطنابة الخزرجي - أحمد, عدنان; يونس, علي (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
هذه الدراسة محاولة للتعريف بشاعر عربي جاهلي قديم , ظلت أخباره وأشعاره طيّ النسيان, لكونه من المقلّين . وقلّما حظي هؤلاء بالاهتمام الذي يستحقونه . وعمرو بن الإطنابة من أشراف الخزرج , كان موطنه مدينة (يثرب) في الحجاز التي على أرضها دارت صراعات وحروب بين الأوس والخزرج عرفت (بالأيام) وقد انعكس ذلك في أشعاره التي استطعتُ جمعها من المصادر التي عدت إليها . وعلى الرغم من قلّة مادته الشعرية , فإنها أضاءت جوانب من شخصيته التي توافرت فيها خصال الشاعر والفارس والملك , فغدا سيّداً في قومه , وقد عكست أبياته تلك الصورة المثلى لهذا السيد , الذي بدا مجسداً منظومة من القيم متكاملة تعارف عليها عصره ومجتمعه القبلي , وهذا ما أعانه على الموازنة بين الحق والقوة فلم ينزلق إلى دائرة الظلم والعدوان . This study is an attempt to introduce an ancient Jahili Arab poet whose news and poems remained forgotten being one of those who produced quite a few works. Rarely have those got the attention they deserve. Amro Bin Alitnaba was of Alkhazraj Noblemen. His residence was in Yathreb City in Alhijaz on whose land battles and wars took place between Alaws and Alkhazraj known as " Alayam / The Days ". This was reflected in his poems that I could gather from consulted references. Though his poetical production was little, it highlighted aspects of his character as a poet, a knight and a king. So he became a Master among his people. His verses reflected that ideal image of this Master who seemed to embody a system of integrated values that became known in his age and his tribal society. This helped him to balance between right and power and to avoid slipping into the circle of inequity and aggression.